New efficient spray technology for cotton crop - Kumar, Santosh; Singh, Manjeet; Narang, Mahesh K (Indian Farming, 2020)
Cotton is an important kharif crop in Punjab as it was grown on 2.84 lakh ha (2018-19). The total production was 11.5 lakh bales with an average yield of 688.38 kg lint/ha. However, in India, total area was 122.38 lakh ha with average yield of 501.47 kg/ha. Although Bt cotton provides effective protection against cotton bollworms, but sucking pests namely whitefly, jassid, aphid and mealy bug are the most serious on Bt cotton and they cause maximum damage during July-September. Whitefly adults and nymphs suck sap from leaves and excrete honey dew on leaves which become sticky. Affected leaves and seed cotton turns black due to development of sooty mould on the plants. Regular monitoring of the crop is must for detection of whitefly incidence.